Quo Vadis Energy Legal Policy towards Equitable and Sustainable Development in Indonesia - Kartika, I Gusti Ayu Putri; Astarini, Ida Ayu; Yasa, Putu Gede Arya Sumerta; Hermanto, Bagus; Kriviņš, Anatolijs (LAW REFORM, 2025)
Indonesia’s energy sector continues to face persistent challenges in the context of rapid economic growth, increasing energy demand, and mounting environmental concerns. Despite the constitutional mandate requiring the state to ensure equitable access to energy and sustainability, existing regulatory frameworks frequently fall short of achieving these objectives. This research aims to examine the legal and policy frameworks governing the energy sector in Indonesia, where energy serves as a critical component of economic development and public welfare.The urgency of this study lies in addressing the disconnect between the normative ideals (das Sollen) of equitable and sustainable energy governance and their actual implementation (das Sein) in current policy practices. The research employs a normative legal method, relying on a literature review of both primary and secondary legal sources, coupled with conceptual and statutory interpretation.The findings indicate that current policies often fail to ensure equitable distribution, meaningful public participation, and adequate environmental protection. Accordingly, legal reforms are necessary to advance justice in energy access and to establish enforceable emission limits and environmental standards. The conclusion drawn from this study underscores the importance of bridging the gap between normative aspirations and practical realities in order to achieve inclusive, sustainable, and just energy governance.